Analysis of ISO 9001:2015 Implementation in Higher Education: A Narrative Literature Review - Amalia, Vyka Nur; Susanti, Desi; Asbari, Masduki (IJOSMAS, 2023)
The purpose of writing this article is a narrative literature review of three articles that discuss the analysis of ISO 9001:2015 implementation in universities, aiming to identify and summarize previously published articles without any criticism for the articles reviewed. The results of the review show that the design and development of a quality management system are built through literature studies related to ISO 9001 requirements and all policies, manuals, guidelines, standards, and work instructions in universities, as well as discussions with all leaders in Faculties, Departments, Study Programs and related Bureaus. Based on the f test, it was obtained that simultaneously all independent variables had a significant effect on the dependent variable of 53,863. Based on the regression test, it can be stated that ISO 9001: 2015 does not have a partial but simultaneous effect when integrated with motivation and competence variables. Quality Management uses to control and assurance of production processes to achieve quality more consistently.